“Useful, not just in the professional world but in everyday life”- Exploring a non-STEM student’s experience in a tertiary-level data analytics unit (Journal of Applied Learning and Teaching, 2024)
This study investigates the transformation in student knowledge pertaining to the study area of ‘data analytics’, and the building of confidence, specifically in non-STEM students, to analyse, interpret, manipulate, and present data to a range of stakeholders using Microsoft Excel. The context of the study is a newly developed, centrally delivered undergraduate data analytics unit, within which a pre-and post-course survey was embedded. These surveys were administered to students across three separate semesters: S2 2022, S1 2023, and S2 2023. The confidence of both non-STEM and STEM students in conducting data analysis was captured. The findings indicate that students benefit from an immersive curriculum where they are exposed to both an understanding of data analytics in a broad global and social context, characterised by rapid technological change, as well as opportunities to master technical skills utilised through Microsoft Excel. The results demystify the notion that non-STEM students are less capable of expanding their depth of knowledge and technological skill development outside their discipline of choice. These results are important in the context of graduate employability and the importance of digital literacy in a rapidly changing world of work.